The P2Y(1) and P2Y(12) receptors mediate autoinhibition of transmitter release in sympathetic innervated tissues - Clara Quintas (2009)
In the sympathetic nervous system, ATP is a co-transmitter and modulator of transmitter release, inhibiting noradrenaline release by acting on P2Y autoreceptors, but in peripheral tissues the subtypes involved have only scarcely been identified. We investigated the identity of the noradrenaline release-inhibiting P2Y subtypes in the epididymal portion of vas deferens and tail artery of the rat. The subtypes operating as autoreceptors, the signalling mechanism and cross-talk with alpha(2)-autoreceptors, was also investigated in the epididymal portion. In both tissues, the nucleotides 2-methylthioATP, 2-methylthioADP, ADP and ATP inhibited noradrenaline release up to 68%, with the following order of potency: 2-methylthioADP = 2-methylthioATP > ADP = ATP in the epididymal portion and 2-methylthioADP = 2-methylthioATP = ADP > ATP in the tail artery. The selective P2Y(1) antagonist 2'-deoxy-N-6-methyladenosine 3',5'-bisphosphate (30 mu M) and the P2Y(12) antagonist 2,2-dimethyl-propionic acid 3-(2-chloro-6-methylaminopurin-9-yl)-2-(2,2-dimethyl-propionyloxymethyl)-propyl ester (30 mu M) increased noradrenaline release per se by 25 +/- 8% and 18 +/- 3%, respectively, in the epididymal portion but not in tail artery. Both antagonists attenuated the effect of nucleotides in the epididymal portion whereas in tail artery only the P2Y(1) antagonist was effective. The agonist of P2Y(1) and P2Y(12) receptors, 2-methylthioADP, caused an inhibition of noradrenaline release that was not prevented by inhibition of phospholipase C or protein kinase C but was abolished by pertussis toxin. 2-methylthioADP and the adenosine A(1) receptor agonist N-6-cyclopentyladenosine were less potent at inhibiting noradrenaline release under marked influence of alpha(2)-autoinhibition. In both tissues, nucleotides modulate noradrenaline release by activation of inhibitory P2Y(1) receptors but in the epididymal portion P2Y(12) receptors also participate. P2Y(1) and P2Y(12) receptors are coupled to G(i/o)-proteins and operate as autoreceptors in the vas deferens where they interact with alpha(2)-adrenoceptors on the modulation of noradrenaline release.